The Analysis of Residents' Behavior, The Condition of Ratproofing Houses and Their Effects on the Incidence of Leptospirosis Cases in Ponorogo Regency - Hanifah Agda Nursitasari (JURNAL KESEHATAN LINGKUNGAN, 2019)
Leptospirosis is a disease with high fatality, it is transmitted by animals infected with Leptospira bacteria either through direct or indirect contact. Ponorogo is one of endemic areas to Leptospirosis whereas the incidence of this zoonotic disease reported annually. The purpose of this study was to analyze the behavior of respondents and ratproofing house conditions against the incidence of leptospirosis in Ponorogo Regency. This research was an observational study with case control research design (ratio of 1: 3 with a comparison of the number of cases of 9 participants and control of 27 participants). The data were obtained by observation and interviews using observation sheets and questionnaires as instruments to obtain information about respondents' behavior and the condition of rats-free houses. The results of statistical tests using chi square showed that contact with standing water is significantly associated with the Leptospiroris incidence with OR = 10.0 (p value=0.03, 95% CI = 1,1 – 91,4) and condition of sewage system (SPAL) also significantly associated with OR = 0.10 (p value 0.02;) 95% CI: 0,01 – 0,79). Poor personal habits such as contact with standing water after working has positive association with odds ratio 10 times higher of causing leptospirosis and the condition of house sewage system (SPAL) that are covered by sewage nets to prevent the entry of mice into the house has negative association or a protective factor against the occurrence of leptospirosis. Suggestions that can be given are educating the general public within the observation area about the dangers of leptospirosis and its prevention, improving the diagnostic ability of Leptosirosis in the Primary Health Care (Puskesmas), improving daily residents behavior or habits by rinsing hands and feet in running water using soap, and closing wire gutters to prevent access rat into the house.